Cross-disciplinary integration of CAT and MT tools into curriculum - Seljan, Sanja (Array, 2014)
The paper deals with educational state-of-art which requires not only highly specialized professionals, but also wide spectrum of interdisciplinary knowledge and skills, especially in the domain of computer-assisted translation (CAT) and machine translation (MT).